Changes in arthropod communities between breeding stages in nests of Great Tits. Issue 4 (3rd January 2022) - Baardsen, Lisa Furu; Matthysen, Erik
Abstract: The biotic and abiotic environments in bird nests change during the nesting cycle as eggs are laid and incubated and nestlings develop and eventually fledge. Nest‐arthropod communities have been studied for many bird species and are commonly sampled after young fledge. However, the population dynamics of arthropods in nests are expected to vary over the nesting cycle as a result of the changing nest environment, in symphony with arthropod life cycles and generation times. Few investigators have examined nest arthropod communities at different stages of the breeding period. We collected nests of Great Tits ( Parus major ) at the egg stage, nestling stage, and after fledging, and extracted nest arthropods using Berlese funnels and identified them to Primary Taxonomic Groups (PTGs). Total arthropod abundance, as well as abundance of fleas, parasitic mites, and adult predatory beetles, was higher during the nestling stage than after fledging. The abundance of beetle mites decreased from the egg stage to fledging, whereas larval predatory beetles and scavenger flies increased. Thus, our results demonstrate important changes in overall abundance, but also in the trophic structure of nest arthropod communities during the nesting cycle. Our results also suggest that nests collected after fledging may give biased information on the abundance of parasites, or nest‐arthropod communities in general, during the nestling stage. RESUMEN: Cambios en las comunidades de artrópodos entre estados reproductivos en nidios de Parus major Los ambientes bióticos y abióticos de los nidos de las aves cambian durante el ciclo de anidación a medida que los huevos son puestos e incubados y los pichones se desarrollan y eventualmente salen del nido. Las comunidades de artrópodos en los nidos han sido estudiadas en muchas especies de aves y son comúnmente muestreadas después de que los pichones abandonan el nido. Sin embargo, se espera que la dinámica poblacional de los artrópodos en los nidos varíe a través del ciclo de anidación, como resultado de cambios en el ambiente del nido, en sincronía con los ciclos de vida de los artrópodos y sus tiempos generacionales. Pocos investigadores han examinado las comunidades de artrópodos en los nidos en diferentes etapas reproductivas. Colectamos nidos de Parus major en la etapa de huevos, en la tapa de pichones y posterior al abandono del nido por los pichones y extrajimos los artrópodos del nido utilizando embudos Berlese y los identificamos hasta los Grupos Taxonómicos Primarios (PTGs). La abundancia total de artrópodos, así como la abundancia de pulgas, piojos parásitos y escarabajos depredadores adultos fue mayor durante la etapa de pichones que después del abandono del nido. La abundancia de escarabajos piojos disminuyó de la etapa de huevos a la etapa de pichones, mientras que larvas de escarabajos depredadores y moscas carroñeras incrementó. Por lo tanto, nuestros resultados demuestran cambios importantes en la abundancia en general, pero también en la estructura trófica de las comunidades de artrópodos en los nidos durante el ciclo de anidación. Nuestros resultados también sugieren que los nidos colectados después de que los pichones han abandonado los nidos pueden dar información sesgada de la abundancia de parásitos o de las comunidades de artrópodos en los nidos en general durante la etapa de pichones.